2015
DOI: 10.1007/s10995-015-1676-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Vitamin A supplementation on child morbidity: A twenty-year time series analysis in the northeastern region of Brazil

Abstract: The present study aimed to determine the prevalence of supplementation between 1987 and 2007, and to measure the impact of this on morbidity. Five sequential cross-sectional studies in a 20-year time span were analyzed. Each had a sample of 8,000 domiciles representative of Ceará, in northeastern Brazil. Data were analyzed with descriptive statistics, followed by bivariate and multivariate analyses. Increases in coverage, ranging from 9.6 to 65.8 % were verified, and the study found that the impact of suppleme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…It found a non-significant mortality rate reduction of 4%, (95% CI 0•89-1•03, p = 0•22), with no specific causes of mortality averted. Other evaluations of the effectiveness of supplementation have found contradictory results, depending largely on the presence of confounding conditions 22,25 . This can be attributed to the immunity modulator effect, or to subgroup effects of vitamin A (known as non-specific effects) 35 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It found a non-significant mortality rate reduction of 4%, (95% CI 0•89-1•03, p = 0•22), with no specific causes of mortality averted. Other evaluations of the effectiveness of supplementation have found contradictory results, depending largely on the presence of confounding conditions 22,25 . This can be attributed to the immunity modulator effect, or to subgroup effects of vitamin A (known as non-specific effects) 35 .…”
Section: Discussionmentioning
confidence: 99%
“…Supplementation at birth has tended to show a small positive effect on child development at three years of age 17 ; however this effect was not statistically significant, and when vitamin A was administered to very low birth weight babies, no effect was observed 18 . In animal models, it was found that the use of megadoses of vitamin A can lead to brain damage 19,20 , injury to motor functions 21 , and modulation of immunity 22 (effects associated with increased oxidative stress [19][20][21]23,24 ). In other studies, vitamin A supplementation has reduced morbidity and mortality in populations with a high prevalence of malnutrition 22,25 .…”
Section: Introductionmentioning
confidence: 99%